New classification of hydronephrosis on 18F-FDG-PET/CT predicts post-operative renal function and muscle-invasive disease in patients with upper urinary tract urothelial carcinoma. (25th September 2018) - Asai, Seiji; Fukumoto, Tetsuya; Watanabe, Ryuta; Koyama, Kanae; Sawada, Yuichiro; Noda, Terutaka; Miura, Noriyoshi; Yanagihara, Yutaka; Miyauchi, Yuki; Miyagawa, Masao; Kikugawa, Tadahiko; Saika, Takashi
Abstract : We classified hydronephrosis based on renal excretion of FDG on FDG-PET/CT. The classification predicted post-operative renal function and pathological outcomes in patients with upper urinary tract urothelial carcinoma. Abstract: Objectives: To evaluate the value of a classification of hydronephrosis on 18 F-flurodeoxyglucose (FDG)-PET/CT in predicting post-operative renal function and pathological outcomes among patients with upper urinary tract urothelial carcinoma. Methods: We retrospectively reviewed 71 patients treated with nephroureterectomy (NU) for upper urinary tract urothelial carcinoma after FDG-PET/CT between 2010 and 2016. Eight patients treated with ureteral stent or nephrostomy at the time of FDG-PET/CT were excluded. We classified hydronephrosis based on renal excretion of FDG as follows: Type 0, no hydronephrosis; Type 1, hydronephrosis with FDG excretion; and Type 2, hydronephrosis without FDG excretion. eGFR was recorded before pre-operataive FDG-PET/CT examination and after nephroureterectomy. Results: Thirty-three patients (52%) had hydronephrosis, classified as Type 1 in 19 patients (30%) and Type 2 in 14 (22%). Type 2 hydronephrosis was associated with ureteral cancer and severe hydronephrosis on CT. Median changes in eGFR before and after nephroureterectomy in patients classified as Type 0, 1 and 2 were −23.9, −18.8 and 2.0 ml/min/1.73 m 2, respectively. On multivariate analysis, Type 2 hydronephrosis was a significant predictor of change in eGFR ( P = 0.001). Rates of muscle-invasive upper urinary tract urothelial carcinoma among Type 0, 1 and 2 patients were 37, 42 and 86%, respectively. On multivariate analysis, Type 2 hydronephrosis was a significant predictor of muscle-invasive upper urinary tract urothelial carcinoma ( P = 0.032, OR 6.491). Conclusions: This classification of hydronephrosis from FDG-PET/CT is simple and useful for predicting post-operative renal function and muscle-invasive disease in patients with upper urinary tract urothelial carcinoma, especially with ureteral cancer. This classification can help in deciding eligibility for lymphadenectomy or perioperative cisplatin-based chemotherapy.